Hailstorm and Human Excreta: Navigating the Hazardous Landscapes in Low-Income Communities in Mangaung, South Africa - Mphambukeli, Thulisile N. (Frontiers in Sustainable Cities, 2020)
This policy brief argues that due to the failure of local municipalities, political instability, and corruption, hazards act synergistically with unequal and complex power relationships to reproduce and disproportionately distribute hazardous landscapes, particularly in the low-income communities of South Africa. It argues that when municipal bureaucrats hide behind a façade of claiming to do something about hazards and the associated challenges they present for low-income communities, but in reality take no action, they reveal their “dangerous mindscapes” which have devastating effects on low-income communities. The author defines “dangerous mindscapes” as the deliberate and consistent insistence that municipal bureaucrats are distributing and will distribute basic services to everyone in South Africa. This consistent insistence is rooted in an ideological mantra that the government is committed to distribute basic services, but in order to justify their failings; they construct basic service provision as dependent on class and citizenship. This study adopted a qualitative research design, grounded on the descriptive phenomenological approach. The study covers the period between 2015 and 2019. Twenty-four (24) in-depth interviews were conducted in the greater Mangaung low-income communities. The brief explores and highlights the climate change-urbanization nexus as politically propelled with devastating spatiality outcomes, where low-income community residents of Mangaung are forced to navigate a hazardous landscape that forces them to “walk at their own risk” because when hailstorms come, the residents are exposed to human excreta from improvised toilets that runs inside their houses and on the streets.